Evidence of large empty lava tubes on the Moon using GRAIL gravity. Issue 1 (13th January 2017) - Chappaz, Loic; Sood, Rohan; Melosh, Henry J.; Howell, Kathleen C.; Blair, David M.; Milbury, Colleen; Zuber, Maria T.
Abstract: NASA's GRAIL mission employed twin spacecraft in polar orbits around the Moon to measure the lunar gravity field at unprecedentedly high accuracy and resolution. The low spacecraft altitude in the extended mission enables the detection of small‐scale surface or subsurface features. We analyzed these data for evidence of empty lava tubes beneath the lunar maria. We developed two methods, gradiometry and cross correlation, to isolate the target signal of long, narrow, sinuous mass deficits from a host of other features present in the GRAIL data. Here we report the discovery of several strong candidates that are either extensions of known lunar rilles, collocated with the recently discovered "skylight" caverns, or underlying otherwise unremarkable surfaces. Owing to the spacecraft polar orbits, our techniques are most sensitive to east‐west trending near‐surface structures and empty lava tubes with minimum widths of several kilometers, heights of hundreds of meters, and lengths of tens of kilometers. Key Points: Multiple lava tube candidates are identified leveraging novel gravity techniques, confirming the existence of such features on the Moon The identified gravity anomalies are robust and persistent through numerous simulations and two independent techniques Leveraging forward modeling techniques, the shape and extent of sample candidates are determined